Assessment and comparison of the effect of oral Channa striatus extract versus glucosamine sulphate administration in serum cartilage and inflammatory marker in knee osteoarthritis patients - Tan, Say Koon; Omar, Julia; Kuttulebbai Naina Mohamed Salam, Sirajudeen; Abdul Kadir, Azidah; Shafii, Noorazliyana; Abdullah, Mohamed Rusli (Penerbit Universiti Sains Malaysia, 2020)
Objectives: Currently, the treatment of osteoarthritis (OA) is to provide pain relief. However, concerns on the side effects with the current treatment has encouraged studies to search for natural products. Channa striatus (CS) is a freshwater fish that is proclaimed as natural remedies to various illnesses by local communities without scientific evidence. Therefore, the objective of this study was to evaluate the effect of oral administration of CS extract (500 mg/day) in knee osteoarthritis (KOA) patients on the level of chondroprotective marker—cartilage oligomeric protein (COMP) and inflammatory marker—Cyclooxgenase-2 (COX-2) and compared it with glucosamine sulphate (GS) treated patients. Methods: This was a randomised and double-blind trial comparing the effect of CS extract (500 mg/day) and GS (1,500 mg/day) treated groups. The number of patients in CS and GS groups were n = 36 and n = 37, respectively. Blood samples were collected at different-time periods (baseline and six months) to assess the level of COMP and COX-2 using commercially available kits. The results were expressed in median and interquartile range (IQR) and P < 0.05 considered as statistically significant. Results: Seventy-three patients enrolled in this study. There were 30 male (41.1%) and 43 female (58.9%) patients with mean age of 53(7) years old. There was a significant reduction of COMP (P < 0.05) and COX-2 (P < 0.05) levels within the groups of GS and CS extract. However, there is no significant median difference in the reduction of COMP and COX-2 levels observed between GS and CS extract treated groups. Thus, CS extract showed as effective as GS in having chondroprotective and anti-inflammatory effect on KOA patients. Conclusion: In conclusion, CS extract on a six months supplementation was found to have reduction properties on the cartilage and inflammatory markers. This could suggest that CS can be an alternative treatment derived from natural source for the treatment of KOA.